2020
DOI: 10.1093/infdis/jiaa305
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Assays in Different Stages of Infection: Comparison of Commercial Enzyme-Linked Immunosorbent Assays and Rapid Tests

Abstract: Abstract We comparatively assessed sensitivities and specificities of 4 commercial enzyme-linked immunosorbent assays (ELISAs) and 2 rapid tests in 77 patients with polymerase chain reaction–confirmed severe acute respiratory syndrome coronavirus 2 infection, grouped by interval since symptom onset. Although test sensitivities were low (<40%) within the first 5 days after disease onset, immunoglobulin (Ig) M, IgA, and total antibody ELISAs increased in sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 7 publications
6
73
0
1
Order By: Relevance
“…Nevertheless, in mild to moderately diseased physicians we demonstrate high agreement rates between SARS-CoV-2-PCR positive results and presence of specific IgA (100%) and IgG (95%) antibodies, which is in accordance with the recently reported detection rates in hospitalized patients, tested with the same ELI-SAs [10].…”
supporting
confidence: 91%
“…Nevertheless, in mild to moderately diseased physicians we demonstrate high agreement rates between SARS-CoV-2-PCR positive results and presence of specific IgA (100%) and IgG (95%) antibodies, which is in accordance with the recently reported detection rates in hospitalized patients, tested with the same ELI-SAs [10].…”
supporting
confidence: 91%
“…17 The results supported previous reports that the sensitivities and specificities of the antibody tests increased weeks after a patient was exposed or developed symptoms associated with COVID-19. 17 Another study examined the sensitivity and specificity of the EDI ELISA for detecting SARS-CoV-2 IgM and IgG antibodies in 64 RT-PCR samples of confirmed COVID-19 patients with serial blood samples at different time points. 15 The study found that the sensitivity of the ELISA test was 5.9% for IgM and 2.9% for IgG 5 days after symptom onset.…”
Section: Austrian Antibody Studiessupporting
confidence: 89%
“…[15][16][17] One study assessed the sensitivity and specificity of four commercial ELISA and two RDT tests in 77 COVID-19 patients compared with the nasopharyngeal RT-PCR. 17 The study found that sensitivities for the ELISA and RDT antibody tests were around 80% within the first week of infection. The specificities for the ELISA tests within 2 weeks were 83% (IgA), 98% (IgG), and 97% (IgM and total antibody).…”
Section: Austrian Antibody Studiesmentioning
confidence: 99%
See 2 more Smart Citations